Pustakawan dan Profesi: Menelaah Profesionalitas Pustakawan dalam Mewujudkan Eksistensi Perpustakaan - Yusniah Yusniah; Annisa Nur Salimah; Mona Elisa; Ghilman Mumtazien (Prodi Perpustakaan dan Sains Informasi, 2023)
Librarians and the profession have a very close relationship. The profession of a librarian requires mature professionalism in his work as a librarian. This study aims to find out how the relationship between librarians and the profession and how a librarian improves his professionalism in carrying out duties in the field of librarianship. This study uses a descriptive qualitative research method by describing the research findings in words. The data collection technique in this research is to use literature study techniques by exploring references through books, articles, and data that support research. So the research results describe that there is a very close relationship between librarians and the profession. As well as in increasing the professionalism of a librarian, sufficient skills and human resources are needed so that they can manage the library properly.